2012
DOI: 10.1016/j.neurobiolaging.2011.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Healthy aging attenuates task-related specialization in the human medial temporal lobe

Abstract: Recent research on aging has established important links between the neurobiology of normal aging and age-related decline in episodic memory, yet the exact nature of this relationship is still unknown. Functional neuroimaging of regions such as the medial temporal lobe (MTL) have produced conflicting findings. Using functional magnetic resonance imaging (fMRI), we have recently shown that young healthy individuals show a stronger activation of the MTL during encoding of objects as compared with encoding of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…There was a significant difference in age between groups, and it is possible that control subjects were more sensitive to cTBS stimulation over PMd than PD patients. Elderly subjects might have higher cerebral activation to compensate for agerelated decline in functionality (Ramsøy et al, 2011). However, it is unclear how the age difference alone could account for the double dissociation between behavioral consequences of cTBS on EBA and PMd across groups.…”
Section: Interpretational Issuesmentioning
confidence: 99%
“…There was a significant difference in age between groups, and it is possible that control subjects were more sensitive to cTBS stimulation over PMd than PD patients. Elderly subjects might have higher cerebral activation to compensate for agerelated decline in functionality (Ramsøy et al, 2011). However, it is unclear how the age difference alone could account for the double dissociation between behavioral consequences of cTBS on EBA and PMd across groups.…”
Section: Interpretational Issuesmentioning
confidence: 99%
“…It was reported that aging reduces cerebral blood flow in association cortices during rest, yet the influence of age on functional brain activation is controversial [20][21][22][23][24][25][26]. Aging differs among individuals, and the areas affected by aging may differ depending on the task [23,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Even when a cognitive task is regressed out and only the residuals are considered, "state" effects may remain. Here, we only considered task-based functional connectivity but have the following caveat: all of our datasets involved encoding of objects or scenes, which we know can be negatively influenced by age (90,91,97). Unfortunately, we do not have access to highresolution data collected during a non-mnemonic task, but advocate replicating this approach in the future to explore the A-P differentiation of the hippocampus and its subfields.…”
Section: Concerns and Limitationsmentioning
confidence: 99%